UNMASKING THE ILLUSIONS OF E-COMMERCE: A CRITICAL EXAMINATION OF CONSUMER EXPLOITATION, ETHICAL FAILURES, AND LEGAL DEFICIENCIES IN DIGITAL TRADE - Zulkifli; Teuku Yudi Afrizal; Nasrianti; Sofyan Jafar; Muhibuddin (Journal of International Islamic Law, Human Right and Public Policy, 2023)
E-commerce is often presented as a symbol of efficiency, accessibility, and consumer empowerment; however, behind this digital convenience lies a complex structure of consumer vulnerability. In Indonesia, the scale of digital trade is significant, with e-commerce transactions reaching IDR 453.75 trillion and 3.71 billion transactions in 2023, while the Ministry of Trade recorded 7,707 consumer reports, including 6,018 complaints, in the same year. These figures indicate that the growth of digital trade has not been fully accompanied by effective consumer protection mechanisms. This article critically examines the illusions of e-commerce by analyzing consumer exploitation, ethical failures, and legal deficiencies in digital sale transactions. Using a juridical-normative and conceptual approach, this study evaluates the issue through consumer protection law, Islamic commercial ethics, human rights norms, and public policy. The analysis argues that consumer exploitation in e-commerce emerges through information asymmetry, misleading advertising, hidden costs, weak refund mechanisms, unfair standard contracts, and limited platform accountability. From the perspective of Islamic law, such practices conflict with the principles of honesty, transparency, mutual consent, and the prohibition of gharar and tadlis. From a human rights perspective, inadequate consumer protection undermines the right to information, economic justice, and effective remedy. Although Indonesia has issued regulations on electronic commerce, including rules on licensing, advertising, supervision, and business actors in electronic trading, regulatory enforcement remains challenged by platform complexity, cross-border transactions, and unequal bargaining power between consumers and digital businesses. Therefore, this article argues that justice in digital trade requires stronger legal reform, ethical business accountability, consumer education, and public policy that places consumer dignity at the center of e-commerce governance.